Open Annotation and Close Reading the Victorian Text: Using Hypothes.is with Students. (1st October 2016) - Kennedy, Meegan
Abstract: Observers of the digital humanities often see them as shifting literary study away from close reading. However, the digital humanities also present opportunities to refine our capabilities for close reading. These digital reading tools, often useful to scholars, may be just as helpful in the classroom. Students working on long Victorian texts often resist close reading. Ideally, they will have multiple low-pressure opportunities to practice this skill. Open annotation provides a frequent, collegial assignment to help students gain the habit of turning to specific moments in the text for their examples. Hypothes.is is an open-source project facilitating group annotation of any online text; it requires users to anchor any comment in a specific text passage while enabling privacy, conversation threads, and easy grading. This essay offers a commentary on open annotation in the classroom, growing out of the particular challenges and rewards of the course where it was used. Students' experiences of the text were indisputably enriched by their work with Hypothes.is, but the assignment works best with careful framing and support due to students' unfamiliarity with the technology.